With the noose around the neck: Marine debris entangling otariid species. (January 2017) - Franco-Trecu, Valentina; Drago, Massimiliano; Katz, Helena; Machín, Emanuel; Marín, Yamandú
Abstract: Plastic debris in marine environments and its impact on wildlife species is becoming a problem of increasing concern. In pinnipeds, entanglements commonly consist of loops around the neck of non-biodegradable materials from fishing gear or commercial packaging, known as "neck collars". These entanglements can cause injuries, death by suffocation and starvation, and therefore they may add to the overall decrease in population. Our objective was to describe the entanglement of two species of otariids ( Arctocephalus australis and Otaria flavescens ) in the South West Atlantic Ocean. These two species have widely different population sizes and contrasting trends, being the O. flavescens population one order of magnitude lower in abundance with a negative population trend. A total number of 47 entangled individuals and the ingestion of a fishing sinker were recorded ( A. australis : n = 26; O. flavescens : n = 22). For A. australis about 40% of the objects came from industrial fishing with which this species overlap their foraging areas, although also its lost or discarded gear can travel long distances. In O. flavescens 48% of observed injuries were very severe, which might indicate that they had been entangled for a long time. More than 60% of the objects came from artisanal and recreational fishing that operates within 5 nautical miles off the coast, which is probably related to coastal foraging habits of this species. Due to the frequent interaction between artisanal fisheries and O. flavescens, it is possible that entangled nets could be active gears. An important contribution to mitigate entanglements can be the development of education programs setting the scenario for effective communication, and exchange with involved fishermen to collect and recycle old fishing nets. Returning to natural fibers or replacement of the current materials used in fishing gear for biodegradable materials can also be a recommended mitigation measure. Graphical abstract: Highlights: More than 60% of the debris come from artisanal and recreational costal fishing. Most of sea lion injuries are deep skin cuts reaching muscular layers. The origin of entanglements are related to foraging habits in both species. Abstract : Marine debris entangling is a potential risk that can affect the otariid populations. We found that the origin of entanglements is related to foraging habits in otariids species.